Phenomenological Study: Grieving Process And Coping Of Mothers With Premature Infant In Neonatal Intensive Care Unit - Anafrin Yugisetyowati (Alma Ata University Press, 2019)
The premature birth of infants is a process that leads to physical unpreparedness, sources of stress, and traumatize effects for the parents. Mostly mothers showed unpleasant memories that interfered the parents' ability to take care of their premature baby. The aim of this study was to explore experience of grieving process and mothers coping during early life care in neonatal intensive care unit. This qualitative research with phenomenological approach used eight participants. Data analysis used in this research was Colaizzi.  The result was the grieving process with various self-coping overview during baby care in the neonatal intensive care unit.  The result of this study recommended professional nurses to conduct an assessment toward parents (the mother). The principle of family centered-care was very important in helping parents to develop therapeutic relationships, providing emotional support, and providing accurate and clear information to parents.   Keywords: Grieving Process, Mothers Coping, Premature Infant Care